Henry Armand Giroux's Thought: An Essential Component of Critical Pedagogy in Religions - Mariani, Evi (Jurnal Theologia, 2022)
Education is essentially a vehicle for honing students' critical and political attitudes in order to create a truly democratic society. Schools as formal educational institutions have so far been interpreted as successors to the status quo, but in fact the role of schools can be more meaningful, namely as a democratic public space, in which teachers play an important role as transformative intellectuals. In the context of transformation, teachers act as designers of classroom conditions and mentors for students to engage in critical dialogue that makes students aware of their current and future roles in a democratic society. Teachers can act as intellectuals when the school system provides opportunities for teachers to be different, create and innovate based on multicultural religions.